Why Indonesian education still inequitable and how the new strategy can solve it? - Leni Lesnawati; Aan Komariah; Cepi Triatna; Asep Suryana; Mochammad Devi Cahya Ruhimat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to design a new strategy to accelerate educational equity through local government. Using a qualitative-descriptive approach, it adopted data triangulation through document review, and in-depth semi-structured interviews with education office practitioners and education planning experts, which is selected purposively. The study lasted 79 days and used a thematic analysis to describe the data. The results: (1) Indonesian national education policy has long set principles for school siting to ensure accessibility; however, local governments still lack standardized procedural guidance for assessing and determining new school locations, resulting in implementation absurdities. (2) A new strategy to address educational inequity was formulated into 3 alternatives: (a) Establishing a local education policy as a standard operating procedure (SOP) for determining new school locations; (b) Multi-actor collaboration among local government, academics, and the community; (c) Creating a location selector application to assess the feasibility of proposed new school sites. The third alternative is special urgency, and it is the most prominent practical implication, because it offers substantial benefits for addressing educational inequity. Although focused on Subang Regency, the study is globally relevant given persistent educational inequity and structural constraints in many countries. Further research is recommended to develop the location selector application.